The simultaneous presence of IL-1B and TNFA two-positions risk haplotypes enhances the susceptibility for celiac disease (2008)
To assess the joint contribution of interleukin 1 beta (IL-1B) and tumor necrosis factor alpha (TNF?) to the genetic risk of developing celiac disease (CD), we analyzed four biallelic polymorphisms of TNFA and IL-1B genes in 228 patients and 244 healthy controls. The individual contribution of TNFA -308A and IL-1B -511C alleles was weak (OR 1.47 and 1.66, respectively) and was null for TNFA -238 A/G and IL-1B +3953 C/T single nucleotide polymorphisms (SNPs). Due to the potential linkage disequilibrium between TNFA, human leukocyte antigen (HLA) -DQA1 and HLA-DQB1 genes, only individuals carrying DQ2 antigen (DQ2-positive) were considered to perform haplotype analyses. Two-position risk haplotypes were first defined by the combined presence of -511C and +3953T alleles for IL-1B (OR 9.402) or -308A and -238A alleles for TNFA (OR 15.389). The TNFA/IL-1B combined haplotype-stratified association analysis showed that the simultaneous presence of TNFA risk and IL-1B non-risk haplotypes (OR 13.32) but not TNFA non-risk and IL-1B risk haplotypes (OR 0.71) is associated with CD. Interestingly, our data suggest that the coexistence of both risk haplotypes seems to work synergistically (OR 29.59), which enhances the risk of developing CD. © 2008 Elsevier Ltd. All rights reserved.